The Trials of Ormond Uren: A Study in Security and Spy Mania. Issue 1 (2nd January 2023) - Bailey, Roderick
Abstract: In 1943, Ormond Uren, an army officer employed in the London headquarters of Britain's Special Operations Executive, was court-martialed and imprisoned after disclosing secret information to a senior member of the Communist Party of Great Britain. The episode has become a staple of writers interested in tales of espionage and questions of loyalty, with Uren's actions routinely presented as those of a spy and traitor. Drawing on MI5 records and other sources, this article argues that those routine images lack convincing evidence to support them; but it also demonstrates that the case retains importance as an example of the risks that secret organizations run when employees' loyalties lie elsewhere.